Quantity, organization, and distribution of chloroplast microsatellites in all species of eucalyptus with available plastome sequence - Andrade, Mateus Chagas; Perek, Matheus; Pereira, Fernanda Bortolanza [UNESP]; Moro, Michele; Tambarussi, Evandro Vagner [UNESP] (FapUNIFESP (SciELO), 2018)
In this study, we quantify and document the distribution and organization of cpSSRs in the chloroplast genome of 31 Eucalyptus species. Our sample included all previously sequenced plastomes of Eucalyptus species available from the NCBI online database. We processed the complete cpDNA sequences and identified mono-, di-, tri-, tetra-, penta-, and hexanucleotide cpSSRs, with the majority of cpSSRs classified as mononucleotide. After genome microsatellite selection, we evaluated the microsatellites for coding and non-coding regions and cpSSRs were predominantly identified in non-coding regions of cpDNA for all nucleotide types. Penta- and hexanucleotide cpSSRs were the least frequent types of microsatellites. We also developed and virtually amplified 60 primers pairs that can be used in studies of Eucalyptus species. Thus, these cpSSR regions can be used in studies assessing the ecology, breeding, and conservation of the genus.
Keywords: Chloroplast DNA; DNA fingerprint; Genetic diversity; Species differentiation